Mechanisms of climate change and related air pollution on the immune system leading to allergic disease and asthma - Sampath, Vanitha; Aguilera, Juan; Prunicki, Mary; Nadeau, Kari C. (Seminars in immunology, 2023)
Climate change is considered the greatest threat to global health. Greenhouse gases as well as global surface temperatures have increased causing more frequent and intense heat and cold waves, wildfires, floods, drought, altered rainfall patterns, hurricanes, thunderstorms, air pollution, and windstorms. These extreme weather events have direct and indirect effects on the immune system, leading to allergic disease due to exposure to pollen, molds, and other environmental pollutants. In this review, we will focus on immune mechanisms associated with allergy and asthma-related health risks induced by climate change events. We will review current understanding of the molecular and cellular mechanisms by which the changing environment mediates these effects. •Fossil fuels are increasing greenhouse gas concentrations.•Greenhouse gases have increased global temperatures by 1.1 °C higher than in 1880.•CO2 levels are high at 421 ppm, levels last seen four million years ago.•Climate change is adversely affecting immune health.•Prevalence of allergies and asthma have increased with climate change.